The history and promising future of phage therapy in the military service. (July 2018) - Gelman, Daniel; Eisenkraft, Arik; Chanishvili, Nina; Nachman, Dean; Coppenhagem Glazer, Shunit; Hazan, Ronen
Abstract : ABSTRACT: The continuous evolvement of bacterial resistance to most, if not all, available antibiotics is a worldwide problem. These strains, frequently isolated from military-associated environments, have created an urgent need to develop supplementary anti-infective modalities. One of the leading directions is phage therapy, which includes the administration of bacteriophages, viruses that specifically target bacteria, as biotherapies. Although neglected in the West until recent years, bacteriophages have been widely studied and clinically administered in the former Soviet Union and Eastern Europe for over a century, where they were found to be incredibly efficient at battling numerous infectious diseases. In this review, we discuss the high potential of phage therapy as a solution for resistant bacterial infectious diseases relating to military medicine. By describing the historical development and knowledge acquired on phage therapy, we define the advantages of bacteriophages for combating resistant bacteria in multiple settings, such as trauma injuries and foodborne illnesses, as a preventive tool and therapy against biological warfare agents, and more. We also present the most recent successful clinical applications of bacteriophages in military settings worldwide. We believe that augmenting military medicine by integrating phage therapy is an important and required step in preparedness for the rapidly approaching post–antibiotic era.